The mediating effect of functional connectivity on the relationship between antisocial parents and children's aggressiveness - Lee, Angel Jia Ying (Nanyang Technological University, 2023)
Increased aggressiveness in individuals can have detrimental effects not only on the individual themselves, but also on their families, friends and even on society. Aggressiveness in individuals could be affected by different factors. The influence of parental factors was heavily researched as parents were the main contributor to children’s development. However, despite the extensive research on parental factors, the study of aggressiveness lacks investigation on neural mechanisms as mediators of the relationship between parental antisocial behaviour (ASB) and children’s aggressiveness. To this end, I attempt to investigate the association between parental ASB, children’s aggressiveness and resting-state functional connectivity (rsFC) networks. The ABCD dataset was used in this study, in which data from a total of 6,008 participants was analysed. Pearson’s correlation, Network-Based Statistics and bootstrapped mediation analyses were conducted. Parental ASB and children’s aggressiveness were found to be positively correlated. 337 edges were found to be significantly associated with children’s aggressiveness, and were further divided into positive and negative networks. Functional connectivity between multiple brain regions was found to be altered. These findings suggest that rsFC plays a mediating role in the relationship between parental ASB and children’s aggressiveness. Further studies involving diverse populations and longitudinal studies can be conducted to supplement existing knowledge in this field.